Obtaining of xanthan gum impregnated of cellulose microfibrils derived from sugarcane bagasse - Gomes, Gleice V. P.; Assis, Denilson de J.; Silva, Jania B. A. da; Santos, Valéria de Carvalho [UNESP]; Costa, Larissa A. S.; Druzian, Janice I. (Elsevier, 2015)
Xanthan gum (XG) is a microbial exopolysaccharide that occupies a prominent place in the market because of its unique properties compared with other microbial gums. When lignocellulosic materials such as sugarcane bagasse (SCB) are used as a carbon source, the degradation of the SCB material can be partial, retaining microfibrils of cellulose in the fermentation broth. These microfibrils can be incorporated into the XG structure. The aim of this work was to select the best concentration of SCB to produce XG and to analyze the characteristics of the biopolymer obtained. The XG produced in the best condition was added to biodegradable films as a reinforcing agent. The SCB was evaluated at the following concentrations: 2, 4, 6, 8 and 10% w/w. The XG produced with 4% w/w SCB provided the best XG, not only for production but also for polymer characteristics. Visualization with transmission electron microscopy (TEM) established the presence of microfibrils in the polysaccharide structure, and the incorporation of XG with microfibrils provided a flexible film with enhanced mechanical properties.
Keywords: Microfibrils; Bioprocess; Xanthan gum; Mechanical properties